Integrating ethnobotany and plant-based Nanoparticles: A bibliometric of their role in sustainable material physics - Solo, Intan Riani; Tungga Dewi, Imelda Zahra; Sri Maharani, Ni Luh (Ethnobotany Research and Applications, 2025)
Background: The convergence of plant-derived nanoparticles and ethnobotanical knowledge represents a promising frontier in material science. Nanoparticles synthesized from plant-based phytochemicals offer a non-toxic, environmentally friendly alternative to conventional chemical methods, aligning with the principles of sustainable nanotechnology. Ethnobotanical insights play a critical role in guiding the selection of plant species, many of which possess long-standing cultural and pharmacological value. Methods: A comprehensive literature search was conducted using the Scopus database for the period 2007–2025. Data were analyzed using Biblioshiny from the bibliometrix library (R-based) tools, including VOSviewer, to map publication trends, author collaborations, and keyword co-occurrences. Results: This study reveals a rapidly growing global research trend integrating plant-derived nanoparticles with ethnobotanical knowledge, highlighting strong international collaborations and a focus on sustainable, bioactive applications such as antioxidants and anticancer properties. India leads this interdisciplinary field, partnering with multiple countries to advance eco-friendly nanotechnologies that combine traditional wisdom and modern science for innovative material and biomedical solutions. Conclusions: There is revolutionary potential for sustainable material science when plant-derived nanoparticles and ethnobotanical knowledge are integrated. This fusion is a strategic step toward developing green nanotechnologies that are both environmentally friendly and culturally informed, fostering innovation that addresses global health and ecological challenges. Keywords: Plant-Derived Nanoparticles, Ethnobotany, Phytochemicals, Material Science, Nanotechnology, Bibliometric